Indikatoren der Ergebnisqualität für die multimodale invasive Behandlung der peripheren arteriellen Verschlusskrankheit (PAVK) - Uhl, C.; Rümenapf, G.; Görtz, H.; Böckler, D.; Behrendt, C. A.; Pleye, J.; Rother, Ulrich (Gefässchirurgie, 2020)
Background: Evaluation of quality indicators in medical treatment strategies is becoming increasingly important, e.g., in the treatment of peripheral artery disease (PAD). Therefore, this study aimed to demonstrate the range of published data of outcome quality depending on different revascularization methods and to define indicators of quality in the treatment of patients with PAD. Methods: Between 1 June 2019 and 25 February 2020, literature regarding open and endovascular revascularization procedures in the treatment of PAD was analyzed by the commission “PAD and diabetic foot” from the DGG e. V. Several outcome quality indicators were defined. A narrative literature search was conducted in order to collect data (mean, range) for the specific indicators. Results: Data regarding outcome quality was assessed. 8 Indicators for outcome quality could be defined for endovascular and open surgical treatment (Claudicatio intermittens [CI]: Early results [30 days]: early graft failure, access side complications; long-term results [5 years]: primary patency, worsening of the Rutherford stadium; chronic critical limb ischemia [CLI]: early results [30 days]: early graft failure, 30 days major amputation; long-term results [1 year]: primary patency, limb salvage). Conclusion: The findings of this study demonstrate the wide range of the published outcome quality after the treatment of peripheral arterial disease (PAD). The Commission “PAD and diabetic foot” from the DGG e. V. defined indicators to report outcome quality. Based on these findings, future registries investigating the outcome of the treatment of PAD are encouraged to use these indicators to generate comparative data.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Amputation; Bypass; Cardiovascular diseases; Diabetes mellitus; Quality indicators